Beta-1 adrenergic receptor signalling during early and late hypertensive cardiac remodelling. (10th June 2022) - Matzer, I; Voglhuber, J; Djalinac, N; Trummer-Herbst, V; Kiessling, M; Fernandes Hollnagel, C; Rech, L; Holzer, M; Ljubojevic-Holzer, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BioTechMed Graz Objective: Chronic activation of β1-adrenergic receptors (β1AR) in response to hypertension is consistently linked to maladaptive remodelling in the heart, however, the underlying mechanisms are not well understood. Here, our aim was to determine the subcellular profile and extent of β1AR expression at baseline and upon acute β-adrenergic stimulation in cardiac myocytes during early- and late-stage cardiac remodelling due to systemic hypertension. Methods: Male Dahl salt-sensitive rats were fed a high-salt diet (HSD; 8% NaCl) for either five or ten weeks to induce early or late hypertensive cardiac remodelling, respectively. Age-, sex- and weight-matched Dahl salt-sensitive rats on a low-salt diet (LSD; 0.3% NaCl) served as controls. To test the effect of conventional anti-hypertensive treatment, a subset of HSD-fed animals received daily doses of the angiotensin-converting-enzyme-inhibitor Imidapril (ACE-I; 1mg/kg/day) starting two weeks after the feeding protocol was switched to HSD. Isolated ventricular myocytes were stimulated either under control conditions or in the presence of β-adrenergic agonist isoprenaline (ISO; 100nM; 1h). Confocal imaging of single cardiomyocytes allowed detailed quantification of β1AR in different cellular compartments. Finally, immunoblotting and microarray analyses were applied to quantify β1AR in the left ventricles of the corresponding groups of animals. Results: In control rats, β1AR was found in a striated pattern throughout the cell typical for T-tubular network and in the perinuclear regions, while its expression significantly dropped upon ISO treatment. During early remodelling, basal β1AR expression was unchanged, but increased on the T-tubules and perinuclear regions upon acute stimulation with ISO. In contrast, late remodelling was marked by reduced β1AR expression at baseline, and significantly blunted increase in response to ISO compared to early time point. Interestingly, daily ACE-I treatment resulted in even more adverse phenotype as compared to untreated HSD-fed rats in early remodelling, but favourable control-like characteristics at late remodelling stage. Immunoblotting and microarrays from left ventricular tissue confirmed the data, where applicable. Conclusion: Taken together, we showed that early hypertensive remodelling is marked by altered β1AR responsiveness upon β-adrenergic stimulation, whereas late remodelling also exhibits altered β1AR expression. ACE-I treatment seemed to interfere with early adaptive mechanisms, thereby worsening the phenotype as compared to untreated HSD-fed animals. However, upon prolonged application, it showed a clear protective effect from pathological molecular alterations at late remodelling. Further experiments involving downstream targets of β1AR signalling are required to fully understand the molecular sequence of events leading to early and late alterations in molecular composition of cardiomyocytes in the hypertensive heart.